Wordplay [videorecording (DVD)] - Creadon, Patrick, 1967-; Shortz, Will, 1952-; Clinton, Bill, 1946-; Stewart, Jon, 1962-; Dole, Robert J., 1923- (IFC Films : Distributed by Genius Entertainment, 2006)
A journey into the world of Will Shortz, the crossword puzzle editor at The New York Times. Shortz has spent his entire lifetime studying, creating and editing puzzles, and has built a huge following along the way including Bill Clinton and Bob Dole.